The Uruk lament - Green, Margret W. (JAOS, 1984)
A Sumerian city lament bewailing the destruction of Uruk is presented in transliteration and translation with critical notes, commentary, and copies. The lament, composed under the aegis of the Isin king Išme-Dagan, was intended to be sung to Inanna and the Anunna-gods in supplication for restoration of an era of peace and prosperity in Sumer and for divine sanction of Išme-Dagan's reign.